Implementasi Multimedia Pembelajaran Interaktif pada Mata Pelajaran Fiqih untuk Meningkatkan Pemahaman Siswa - Ahmad Izza Muttaqin; Adam Mustakim (Tarbiyatuna Kajian Pendidikan Islam, 2025)
The study aims to describe the implementation of multimedia interactive learning on fiqih subjects in class VIII in improving student understanding at Mabadi’ul Ihsan Karangdoro MTs. The type of research used is a descriptive qualitative approach, and the data collection procedure uses three techniques of observation, interview, and documentation. Process of data analysis through data reduction, data presentation, and drawing conclusions. for verifying the validity of data using source triangulation. The results of research are known that the implementation of multimedia interactive learning on fiqih subjects is first, the preparation of teachers preparing learning devices, preparing materials and checking media tools. Second, the performance of the teacher conditioning and guiding during the learning process. Third, the teacher’s assessment provides the issues that have already been described in the application. As for the supporting factor of the implementation of multimedia interactive learning, the presence of a professional teacher able to use a fun media, from the students themselves this media can attract interest and motivation of his learning. the inhibitory factor, not available materials especially on PAI subjects, and access to the internet network available in the school is still less than maximum.